Latin American Study of Hereditary Breast and Ovarian Cancer LACAM: A Genomic Epidemiology Approach - Oliver, Javier; Quezada Urban, Rosalía; Franco Cortés, Claudia Alejandra; Díaz Velásquez, Clara Estela; Montealegre Paez, Ana Lorena; Pacheco-Orozco, Rafael Adrián; Castro Rojas, Carlos; García-Robles, Reggie; López Rivera, Juan Javier; Gaitán Chaparro, Sandra; Gómez, Ana Milena; Suarez Obando, Fernando; et al. (Frontiers in Oncology, 2019)
PURPOSE: Hereditary Breast and Ovarian Cancer (HBOC) syndrome is responsible for approximately 5-10% of all diagnosed breast and ovarian cancers. Breast cancer is the most common malignancy and the leading cause of cancer-related mortality among women in Latin America (LA). The main objective of this study was to develop a comprehensive understanding of the genomic epidemiology of HBOC throughout the establishment of The Latin American consortium for HBOC-LACAM, consisting of specialists from 5 countries in LA and the description of the genomic results from the first phase of the study. METHODS: We have recruited 403 individuals that fulfilled the criteria for HBOC from 11 health institutions of Argentina, Colombia, Guatemala, Mexico and Peru. A pilot cohort of 222 individuals was analyzed by NGS gene panels. 143 genes were selected on the basis of their putative role in susceptibility to different hereditary cancers. Libraries were sequenced in MiSeq (Illumina, Inc.) and PGM (Ion Torrent-Thermo Fisher Scientific) platforms. RESULTS: The overall prevalence of pathogenic variants was 17% (38/222); the distribution spanned 14 genes and varied by country. The highest relative prevalence of pathogenic variants was found in patients from Argentina (25%, 14/57), followed by Mexico (18%, 12/68), Guatemala (16%, 3/19) and Colombia (13%, 10/78). Pathogenic variants were found in BRCA1 (20%) and BRCA2 (29%) genes. Pathogenic variants were found in other 12 genes, including high and moderate risk genes such as MSH2, MSH6, MUTYH and PALB2. Additional pathogenic variants were found in HBOC unrelated genes such as DCLRE1C, WRN, PDE11A and PDGFB. CONCLUSION: In this first phase of the project, we recruited 403 individuals and evaluated the germline genetic alterations in an initial cohort of 222 patients among 4 countries. Our data show for the first time in LA the distribution of pathogenic variants in a broad set of cancer susceptibility genes in HBOC. Even though we used extended gene panels, there was still a high proportion of patients without any detectable pathogenic variant, which emphasizes the larger, unexplored genetic nature of the disease in these populations.